Building an information security awareness program : defending against social engineering and technical threats - Gardner, Bill (Bill G.); Thomas, Valerie (Information security consultant) (Waltham, Massachusetts : Syngress, 2014)
The best defense against the increasing threat of social engineering attacks is Security Awareness Training to warn your organization''s staff of the risk and educate them on how to protect your organization''s data. Social engineering is not a new tactic, but Building an Security Awareness Program is the first book that shows you how to build a successful security awareness training program from the ground up. Building an Security Awareness Program provides you with a sound technical basis for developing a new training program. The book also tells you the best ways to.
Print version record.
Includes bibliographical references and index.
Keywords: Information storage and retrieval systems -- Security measures; Online social networks -- Security measures; Safety education; Occupational training; Situational awareness; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Information storage and retrieval systems -- Security measures; Occupational training; Safety education; Situational awareness; Computer Security; Social Sciences; Electronic books